A NEED ANALYSIS IN ENGLISH MATERIAL FOR XI GRADE OF BEAUTY PROGRAM - Padmawati, L. W.; Dewi, K. Sintya (Universitas Pendidikan Ganesha, 2021)
Needs analysis aims to identify what English students should learn. However, there are still many teachers who have not analyzed the material needs of students. The material used by the teacher is too general for students. Students do not get English for specific purposes for particular majors. This results when students find it challenging to communicate with guests in certain areas. This study aims to analyze the English material and analyze the suitability of the English language material based on the ESP principles. This study used the descriptive qualitative method. The study subjects were students of the class XI beauty program—the use of questionnaires and document checklists as data collection instruments. The study results indicate that students need unique English materials and special English skills in the tourism sector, especially in beauty spas. Furthermore, based on the document checklist, the English teaching materials in the beauty program are not by the ESP concept because the data shows that the teaching materials are too general and not close to the student's field. Therefore, students hope that the school can design an ESP program to improve competence in beauty spa activities.